Diagnosis of thalassemia on dried blood spot samples by high performance liquid chromatography - Pornprasert S. (2017)
High performance liquid chromatography (HPLC) on fresh lysates is the standard test for identification of thalassemia. Samples in the form of dried blood spot(s) (DBS) mailed to reference laboratories where HPLC is available could be an alternative. Hemoglobin (Hb) on DBS at day 1, 7, 15 and 30 were analyzed by HPLC and compared to those analyzed from fresh liquid whole blood at day 0. A 100 consistent interpretation of β-thalassemia (β-thal) trait and β-thalHb E disease between liquid whole blood and DBS was observed when analyzing Hb A2 on DBS at a level of 2.79.9 in conjunction with a lower MCV ( < 80 fL) and MCH ( < 27 pg) and analyzing β-thalHb E by using Hb E and Hb F at a level of 3048 and > 10, respectively. Therefore, our results show that detection of thalassemia carriers using DBS is possible and is the alternative of choice in a low resource setting. © 2010 Informa UK Ltd.